Language and Emotion. - Schiewer, Gesine Lenore; Altarriba, Jeanette, 1964-; Ng, Bee Chin (Handbücher Zur Sprach- und Kommunikationswissenschaft / Handbooks of Linguistics and Communication Science [HSK], 2022)
The series Handbooks of Linguistics and Communication Science is designed to illuminate a field which not only includes general linguistics and the study of linguistics as applied to specific languages, but also covers those more recent areas which have developed from the increasing body of research into the manifold forms of communicative action and interaction.